A General Equilibrium Assessment of the Economic Impact of Deep Trade Agreements - Fontagne, Lionel; Rocha, Nadia; Ruta, Michele; Santoni, Gianluca (World Bank, Washington, DC, 2021)
This paper explores the economic impacts of preferential trade agreements, focusing on the provisions they contain, beyond phasing out tariffs. Clustering 278 preferential trade agreements based on 906 provisions grouped into 18 policy areas, three clusters are obtained for which a trade elasticity to preferential trade agreement is estimated using structural gravity. A series of full general equilibrium counterfactual situations for endowment economies is simulated, revealing the economic impacts of deepening existing trade agreements and signing new ones—that is, the intensive and extensive margins of preferential trade agreements. The paper illustrates the method with a general deepening of existing preferential trade agreements worldwide. Focusing on the examples of the Latin America and the Caribbean and East Asia and Pacific regions, the paper shows that deepening preferential trade agreements leads to higher trade and welfare effects than signing new ones.